Effect of DNA methylation on the osteogenic differentiation of mesenchymal stem cells: concise review - Lai, Zhihao; Shu, Qing; Song, Yue; Tang, Ao; Tian, Jun (Frontiers in Genetics, 2024)
Mesenchymal stem cells (MSCs) have promising potential for bone tissue engineering in bone healing and regeneration. They are regarded as such due to their capacity for self-renewal, multiple differentiation, and their ability to modulate the immune response. However, changes in the molecular pathways and transcription factors of MSCs in osteogenesis can lead to bone defects and metabolic bone diseases. DNA methylation is an epigenetic process that plays an important role in the osteogenic differentiation of MSCs by regulating gene expression. An increasing number of studies have demonstrated the significance of DNA methyltransferases (DNMTs), Ten-eleven translocation family proteins (TETs), and MSCs signaling pathways about osteogenic differentiation in MSCs. This review focuses on the progress of research in these areas.